The Effect of Planting Distance and Urea Fertiliser Dosage on the Growth of Lemongrass in a Polyculture System - Yustina Sri Sulastri; Kurnia Selekta Etika Harefa; Marta Yulina Munte (Agroprimatech, 2025)
This study aimed to determine the effect of planting distance and urea fertilizer dosage on the growth of fragrant lemongrass in a polyculture cultivation system under rubber stands. The research was conducted on Jl. Sei Putih Rispa, Kelapa Satu Village, Galang District, Deli Serdang Regency, North Sumatra, at an altitude of about 65 m above sea level from May to August 2025. The experiment used a factorial Randomized Block Design (RBD) with two factors: planting distance and urea dosage. Planting distance consisted of three levels, namely J1 (20 × 40 cm), J2 (20 × 60 cm), and J3 (20 × 80 cm). Urea dosage consisted of four levels: U0 (0 g/plant), U1 (5 g/plant), U2 (10 g/plant), and U3 (20 g/plant). These treatments produced 12 combinations with three replications, resulting in 36 plots, each with four samples, totaling 144 plants. Observations were made at harvest, including root fresh weight, shoot fresh weight, root volume, root dry weight, shoot dry weight, and root-shoot ratio. The results indicated that planting distance significantly influenced root fresh weight, shoot fresh weight, root volume, root dry weight, and shoot dry weight, whereas urea dosage did not show a significant effect on the measured parameters. The most favorable planting distance for fragrant lemongrass growth was 20 × 80 cm, followed by 20 × 60 cm, suggesting that wider spacing supported better plant development in a polyculture system under rubber stands.